(untitled) (Journal of Medical & Health Sciences Review, 2025)
Cadmium (Cd²⁺) must be effectively removed from effluent because of its high toxicity and persistence in aquatic settings. In this work, Undaria pinnatifida was used to create a sulfated fucoidan hydrogel (FUC-HG), which was then tested as a high- performance bioadsorbent for Cd2+ sequestration. A maximal adsorption capacity of approximately 50 mg g⁻¹ was made possible by the hydrogel’s heterogeneous surface with numerous active binding sites. While kinetic analysis followed the pseudo-second- order model (R²=0.9876), confirming chemisorption as the main mechanism, equilibrium data fitted the Freundlich isotherm (R²=0.9441), showing multilayer adsorption. According to thermodynamic investigations, the reaction was spontaneous, endothermic, and entropy-driven, which is in line with chemical interactions between the hydroxyl and sulfated functional groups of FUC-HG and Cd²⁺ ions. Elovich and intraparticle diffusion investigations, which emphasised surface binding followed by pore diffusion, provided additional evidence for sequential uptake. Over several cycles, the hydrogel showed outstanding durability and reusability while retaining a high adsorption efficiency. These findings establish FUC-HG as an economical, selective, and eco- friendly bioadsorbent with great promise for real-world use in industrial heavy metal remediation and wastewater treatment.